Knowledge, attitudes, and practices among Florida bird rehabilitators regarding Highly Pathogenic Avian Influenza (HPAI) H5N1 - Mills, Zach (My University, 2023)
Highly pathogenic avian influenza (HPAI) type A (H5N1), also colloquially known as “Bird Flu,” is a highly contagious zoonotic viral disease of birds. First identified in a goose in China in1996, HPAI A(H5N1), referred to as HPAI H5N1, crossed over to humans with the first case reported in Hong Kong in 1997. Since these initial cases, scientists have identified HPAI H5N1 in North America, Europe, Africa, the Middle East, and Asia. The first case of HPAI H5N1 in the United States occurred in 2015 in waterfowl. The current outbreak of HPAI H5N1 started at the end of 2020 and is responsible for the culling deaths (euthanasia) of nearly 60 million birds in the United States and another 50 million birds in Europe, has been identified in 47 states, and has infected over 20 different mammals in addition to humans. Veterinarians in Florida first detected HPAI H5N1 in January 2022 from a hunter-harvested, blue-winged teal in Palm Beach County, and they have now identified the virus in over 2,000 wild birds in 37 counties across Florida. In Florida, there have been no human fatalities to date, and no commercial poultry operations have had an outbreak, yet influenza viruses easily mutate, and it is one mutation away from a variant that could be deadly to more birds, animals, and humans. One of the most exposed human populations in Florida to HPAI H5N1 are wildlife rehabilitators, especially avian rehabilitators. Because of this potential risk for exposure to HPAI H5N1 to avian rehabilitators, the Florida Commission of Wildlife (FWC) has taken increased measures to educate this population of individuals to reduce their risk of exposure and to reduce the risk of inadvertent spread of HPAI H5N1 in avian rehabilitation facilities. A first-in-kind survey of avian rehabilitation facilities was conducted in the summer of 2023 to assess the knowledge, attitudes, and practices among Florida bird rehabilitators regarding HPAI H5N1 to better inform the FWC on what information needs to be conveyed to this cohort of individuals, how this group prefers to receive its training and education, and what limitations exist for this group regarding protection of their employees, the birds in their care, and other birds with whom they might potentially contact.
Keywords: Highly Pathogenic Avian Influenza H5N1; Avian Rehabilitators; Infectious Disease; Zoonotic; Wildlife